2020
DOI: 10.3389/fbioe.2020.00154
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Three-Level Cervical Hybrid Surgery to Prevent Adjacent Segment Disease: A Finite Element Study

Abstract: Hybrid surgery (HS) allows surgeons to tailor fusion and arthroplasty in the treatment of multiple-level cervical disc degeneration. However, the decision making of selecting either ACDF or ADR for each level in three-level HS remains controversial and has not been fully investigated. This study was aimed to optimize three-level cervical hybrid constructs by systematically investigating their biomechanical properties and their effect on adjacent levels. A finite element model of cervical spine (C2-C7) was deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 40 publications
(50 reference statements)
4
24
0
Order By: Relevance
“…The effect of the arthroplasty level and construct type was unclear, with no significant difference in outcomes noted between the combinations. 36 However, this likely reflects the low numbers in the different treatment groups. As noted, the most common construct was a 3-level cervical hybrid, with a 1-level CTDR cranially, and ACDF at the 2 caudal levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the arthroplasty level and construct type was unclear, with no significant difference in outcomes noted between the combinations. 36 However, this likely reflects the low numbers in the different treatment groups. As noted, the most common construct was a 3-level cervical hybrid, with a 1-level CTDR cranially, and ACDF at the 2 caudal levels.…”
Section: Resultsmentioning
confidence: 99%
“…Motion preservation allows load sharing, which provides a more favorable biomechanical environment at adjacent segments compared with that afforded by fusion surgery, thereby reducing the compensatory hypermobility and peak stresses that would otherwise accelerate the processes of RASP and CASP. [33][34][35][36][37][38][39][40] Currently, there are only limited reported studies on cervical hybrid surgery that tend to be short-term studies of small patient cohorts. 41,42 The existing reports, and subsequent systemic reviews synthesizing those reports, demonstrate cervical hybrid surgery to have equivalent outcomes and functional recovery compared with multilevel ACDF, superior range of motion, and favorable improvements in Neck Disability Index (NDI).…”
Section: Introductionmentioning
confidence: 99%
“…The contact method between facet cartilages was modeled as frictional contact, with the surface-to-surface method. Additionally, the friction coefficient was 0.1 ( Wong et al, 2020 ; Wo et al, 2021 ). The contact between UJs and cortical bone was identical to facet cartilages.…”
Section: Methodsmentioning
confidence: 99%
“…Finite element analysis (FEA) has been widely used to evaluate the biomechanical effect of surgeries ( Ottardi et al, 2016 ; Wang B. et al, 2019 ; Wong et al, 2020 ). FEA can also facilitate the biomechanical assessment of spinal disease, such as degeneration, compression fracture, and scoliosis ( Natarajan and Andersson, 2017 ; Dupuis et al, 2018 ; Nakashima et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the range of motion (ROM), intradiscal pressure (IDP), facet joint stress, and internal fixation device stress were calculated and analyzed to evaluate the biomechanical effect of different surgical approaches. Several previous studies indicated that FEA enabled the evaluation of the ROM and IDP of the adjacent segments to predict the risk factors of adjacent segment degeneration after cervical or lumbar surgeries ( Ke et al, 2019 ; Wang B. et al, 2019 ; Hua et al, 2020 ; Wong et al, 2020 ). However, the studies only focused on the postoperative effect of internal fixation to evaluate the biomechanical advantages and disadvantages of surgical treatment.…”
Section: Introductionmentioning
confidence: 99%